Maternal mortality in modern world - E. I. Baranovskaya (Акушерство, гинекология и репродукция)
Aim: to analyze the causes and level of global maternal mortality (MM) according to the data published within the last 7 years.Materials and Methods. Search for publications in the PubMed/MEDLINE database was conducted according to the criteria: metaanalysis, free full-text, English, 2015–2021 period. The PICO principle (Patient/Problem, Intervention, Comparison, Outcome) and the keywords "maternal mortality causes", "maternal death causes", "maternal outcomes" were used. The search was finished on October 13, 2021 after retrieving 137 results.Results. The rate of MM and cause pattern has been changing during COVID-19 pandemic. The first weeks of the COVID-19 lockdown showed that in-hospital mortality among pregnant women increased from 0.13 up to 0.20 % (p = 0.01) and in MM the proportion of respiratory diseases elevated up to 32 % versus 5.6%. Certain geographic regions of the world showed that MM due to COVID-19 reached extremely high values extending 3399 per 100,000 live births as well as increased general MM rate. Heart and vascular diseases (pericarditis, myocardial infarction, thromboembolism) have a significant position among the causes of MM. The rate of MM due to cardiovascular disease was inversely related to the population income level. Cardiomyopathy is the cause of death in 4 % (95 % confidence interval (95 % CI) = 2–7) of mothers in developed countries and 14 % (95 % CI = 10–18) in developing countries. The mortality rate 6 weeks after delivery among women with pregnancy-related myocardial infarction was 5.03 % (95 % Cl = 3,78–6,27), whereas it associated with thromboembolism among women with a mechanical heart valve was related to the agent used to prevent thrombosis, ranging from 0.9 (95 % CI = 0.1–1.6) for vitamin K antagonists up to 3.4 (95 % CI = 0–7.7) for unfractionated heparin per 100 pregnancies with a mechanical heart valve. After 2000, the proportion of anesthesia among immediate MМ causes decreased from 3.5 % (95 % CI = 2.9–4.3) down to 2.4 % (95 % CI = 1.9–2.9) in low- and middleincome countries. High MM odds due to maladjusted pregnancy are still observed: OR (odds ratio) = 17 (95 % CI = 9.6–28.8) for hypertension, OR = 3.70 (95 % CI = 1.72–7.99) for HELLP syndrome with acute kidney injury. Severe obstetric complications cause MM in sub-Saharan Africa and South Asia: bleeding (OR = 28.8; 95 % CI = 20.3–40.7), preeclampsia or eclampsia (OR = 9.13; 95 % CI = 6.10–13.7), maternal infections in antenatal period (OR = 2.80; 95 % CI = 1.63–4.80). About 67 % of pregnant women in such countries obtain no antenatal care (OR = 2.80; 95% CI = 1.63–4.80), predominantly giving birth at home in sub-Saharan Africa. In Ethiopia, ММ results from obstructed home delivery resulting in maternal death in 17.27 %, where uterine rupture is cause of death in 7.75 % of women.Conclusion. The COVID-19 pandemic contributed a lot to MM. Diseases of the cardiovascular system markedly elevate the MM risk and long-term mortality after delivery. For countries with traditionally home births in the absence of medical care, a high MM remains due to complicated and protracted labor complicated by uterine rupture.